(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2019)
This paper presents a model-based parallelization approach to parallelize embedded systems on single-ISA heterogeneous multicore processors, especially processors with the ARM big.LITTLE architecture, wherein the core assignment of the Simulink blocks is determined based on the control design constraints and characteristics of the big.LITTLE architecture. The proposed approach uses a hierarchical clustering method on Simulink blocks to reduce the problem scale, and an integer linear programming (ILP) formulation to determine the core assignment solution, considering load balancing and minimization of inter-core communication across cores with different performances. Finally, we generate the parallel code of the model based on the core assignment solution for execution on the processors. We evaluate the proposed approach by comparing it with existing methods and generating the parallel code on a single-board computer with the big.LITTLE architecture to determine its effectiveness.